2022
DOI: 10.1371/journal.pone.0266000
|View full text |Cite
|
Sign up to set email alerts
|

Effects of action observation and motor imagery of walking on the corticospinal and spinal motoneuron excitability and motor imagery ability in healthy participants

Abstract: Action observation (AO) and motor imagery (MI) are used for the rehabilitation of patients who face difficulty walking. Rehabilitation involving AO, MI, and AO combined with MI (AO+MI) facilitates gait recovery after neurological disorders. However, the mechanism by which it positively affects gait function is unclear. We previously examined the neural mechanisms underlying AO and MI of walking, focusing on AO+MI and corticospinal and spinal motor neuron excitability, which play important roles in gait functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…In this condition, facilitation of corticospinal excitability in the TA muscle was observed 30 min after the intervention ( p < 0.05), while no facilitation resulted in the FES only condition ( p > 0.05, Figure 4A ). Because the intervention using only AO + MI of walking did not change corticospinal excitability ( Kaneko et al, 2022 ), our results suggest that the facilitation was driven by the walking phase-dependent synchronization of cortical activation during AO + MI and sensory inputs induced by FES. This is supported by previous studies reporting that the timing of cortical activation and sensory inputs is an essential factor in facilitating corticospinal excitability ( Stefan, 2000 ; Mrachacz-Kersting et al, 2007 ).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In this condition, facilitation of corticospinal excitability in the TA muscle was observed 30 min after the intervention ( p < 0.05), while no facilitation resulted in the FES only condition ( p > 0.05, Figure 4A ). Because the intervention using only AO + MI of walking did not change corticospinal excitability ( Kaneko et al, 2022 ), our results suggest that the facilitation was driven by the walking phase-dependent synchronization of cortical activation during AO + MI and sensory inputs induced by FES. This is supported by previous studies reporting that the timing of cortical activation and sensory inputs is an essential factor in facilitating corticospinal excitability ( Stefan, 2000 ; Mrachacz-Kersting et al, 2007 ).…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, the present study focused on AO + MI of walking combined with FES of ankle dorsiflexion and plantar flexion (i.e., PNS of the common peroneal and tibial nerves). Our recent study found no modulation of corticospinal and spinal motor neuron excitability after a 20-min AO + MI of walking alone ( Kaneko et al, 2022 ), indicating that AO + MI by itself exerted minor effects on neural activity; however, we implied that combining it with additional treatment may induce transient changes in electrophysiological measures of corticospinal and spinal excitability. The purpose of the present study is to apply FES for dorsiflexion and plantar flexion simultaneously with and without AO + MI of walking and to investigate its transient effect on corticospinal and spinal reflex excitability, which is related to gait functions.…”
Section: Introductionmentioning
confidence: 69%
“…The current results agree with studies reporting beneficial effects induced by early sleep on the learning process of trained motor skills in older adults 23 , 24 . The opportunity enhance gait and balance abilities through the delivery of early sleep after AOMI sessions represents the innovative aspect of this study, since previous literature data have reported limited AOMI effects on gait and balance performance in older adults 18 , 21 . In addition, the achievement of such sleep-dependent benefits after a training based on the solely systematic observation and imagination of motor tasks in the absence of imitation, further increases the relevance and applicability of this AOMI-training modality.…”
Section: Discussionmentioning
confidence: 99%
“…Such phenomenon has been also reported to be dependent by walking phases, showing the AOMI ability to emulate the cortical activity induced by actual walking 16 . In addition, an increase in corticospinal excitability has been also reported during AOMI of walking, although this effect seems to be transient after a single session 17 , 18 . Interestingly, the aforementioned modulations in terms of brain activation pattern and corticospinal excitability have been reported to be higher during AOMI, when compared to action observation and motor imagery alone 14 17 .…”
Section: Introductionmentioning
confidence: 93%
“…There is a rich literature on motor neuron plasticity in this preparation, some of which reports PKC-dependent mechanisms (Cai et al, 2008; Fulton et al, 2008; Glanzman, 2008; Villareal et al, 2009; Reissner et al, 2010; Jin et al, 2011; Bougie et al, 2012; Choi et al, 2014; Hu et al, 2015, 2017a; Ferguson et al, 2019; Alexandrescu and Carew, 2020). Also in mammals (including humans) motor neuron plasticity in the spinal cord is a readily observable phenomenon in non-clinical and clinical settings (Wolpaw and Lee, 1989; Wolpaw et al, 1989; Carp and Wolpaw, 1994; Carp et al, 2001; Wang et al, 2006; Wolpaw, 2012; Eftekhar et al, 2018; Kaneko et al, 2022; Rochat et al, 2022; Simonyan et al, 2022). The discovery of aPKC-dependent plasticity in Drosophila motor neurons expands this body of literature to a genetically tractable organism and inasmuch as clinical practice relies on motor neuron plasticity, may even help instruct the development of clinical applications.…”
Section: Discussionmentioning
confidence: 99%